(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
To prepare wearable personal thermal management fabric, conductive yarn was synthesised by in-situ polymerisation of polyaniline (PANI) and electroless silver plated nanoparticles (AgNPs) using acrylic (PAN) yarn as substrate. Subsequently, AgNPs/PANI/PAN conductive yarns of different structures are woven. SEM, XRD and FT-IR characterised the structure and properties of AgNPs/PANI/PAN yarns. The resistance and temperature of fabric at different voltages were measured by four probe testers and a thermal infrared imager. The results show that when AgNO_3 concentration is 10 g/L, the resistance of AgNPs/PANI/PAN conductive yarn is 0.81 Ω/cm. At the same warp and weft density, the resistance of the satin fabric is 0.272 Ω/sq, and the resistance of the plain fabric is 0.404 Ω/sq. When the voltage is 0.8 V, the equilibrium temperature of the satin fabric reaches 77.6 ^◦C, and that of the plain fabric reaches 63.4^◦C. With the increase of applied voltage, the heat loss of satin fabric decreases during the heating process.